Pengaruh Circuit Training Terhadap Peningkatan Vo2max bagi Atlet UKM Dayung Universitas Tanjungpura Pontianak - Lihong, Rudianto; Ynitaningrum, Wiwik; Ali, Rizki Hazazi; Hidasari, Fitriana Puspa; Pranata, Doni; Yadi, Januar Inggar (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This study aims to determine the effect of circuit training exercises on increasing Vo2max for athletes at the UKM Rowing Tanjungpura University Pontianak and to find out whether circuit training exercises are effective in increasing Vo2max for athletes UKM Rowing Tanjungpura University Pontianak. This type of research is experimental research. The research sample consisted of 14 people. The instrument used is the bleep test. This research shows that circuit training can increase the Vo2max of Rowing UKM athletes at Tanjungpura University, Pontianak. The independent t-test shows that the sig value is 0.001 < 0.05. Thus, HO is rejected, and Ha is accepted. Circuit training exercises are also effective in increasing Vo2max. The paired t-test shows that the experimental group has a Sig value. (2-tailed) was 0.000 < 0.05, while the control group had a Sig value. (2-tailed) of 0.217 > 0.05. So, there is a significant comparison between the Experimental and Control groups regarding the increase in Vo2max. In conclusion, circuit training exercises significantly influence the increase in the Vo2max of Rowing UKM athletes at Tanjungpura University, Pontianak. Circuit training exercises effectively increase the Vo2max of Rowing UKM athletes at Tanjungpura University, Pontianak. Keywords: Circuit Training, Rowing Sports , Vo2max,